How the Maastricht regime fosters divergence as well as fragility - Jörg Bibow (Levy Economics Institute of Bard College, 2006)
This paper investigates the phenomenon of persistent macroeconomic divergence that has occurred across the eurozone in recent years. Optimal currency area theory would point toward asymmetric shocks and structural factors as the foremost candidate causes. The alternative hypothesis pursued here focuses on the working of the Maastricht regime itself, making it clear that the regime features powerful built-in destabilizers that foster divergence as well as fragility. Supposed adjustment mechanisms actually have turned out to undermine the operation of the currency union by making it less optimal, that is, less subject to a one-size-fits-all monetary policy and common nominal exchange rate, in view of the resulting business cycle desynchronization and related build-up of financial imbalances. The threats of fragility and divergence reinforce each other. Without regime reform these developments could potentially spiral out of control, threatening the long-term survival of EMU.
Keywords: E52; E58; E61; E63; E64; E65; 330; Economic and monetary union; optimum currency area theory; wageprice flexibility; divergence; imbalances